Unveiling the avian community structure, habitat preference, and conservation concerns in the sal forest of central bangladesh - Jaman, Mohammad Firoj; Shome, Ashikur Rahman; Alam, Md Mahabub; Mia, Tanvir; Ilma, Umme Habiba; Tareq, Mehedi Hasan; Rabbe, Md Fazle (Dhaka University Journal of Biological Sciences, 2024)
A study on avifaunal diversity was conducted in Bhawal National Park, Gazipur, Bangladesh, from November 2020 to October 2021 using direct field observation. The study area was divided into five sites based on the habitat structure. A total of 138 bird species and 1,808 individuals were directly counted, representing 17 orders and 49 families. The order Passeriformes and the family Cuculidae had the highest number of species. During the winter season, the richness, abundance, and diversity was the maximum (116 species, 1132 individuals, H= 4.151, Ds= 0.976), with resident bird surpassing migratory species. Among the five study sites, the deep forest area exhibited the greatest number of bird species (75 species, H= 3.983, Ds= 0.975) and trees were the used microhabitat for the birds (101 species, 1521 individuals, H= 4.1, Ds= 0.977). Jungle Babbler (Turdoides striata) had the maximum relative abundance and the ten most abundant species constituted 36.7% of total individuals. A total of 25 habitat generalist species was observed using more than one habitat during the study, while the rest were found in single habitat. Among all the bird species, 136 were Least Concern, one was Near Threatened, and one was Data Deficient. Based on the observation status, it was determined that the majority of bird species (97 species, 70.28%) were classified as few, while 25 species (18.11%) were as uncommon, 12 species (8.69%) as common, and 4 species (2.89%) as very common. The area was noted for its widespread use for recreational activities, and the disturbance caused by visitors lacking awareness poses a significant threat to the local bird population and biodiversity. Dhaka Univ. J. Biol. Sci. 33(1): 1-21, 2024 (January)